2014
DOI: 10.4244/eijv10i2a34
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactivity and cardiovascular events after percutaneous coronary intervention in patients with stable coronary artery disease: the Stent Thrombosis In Belgium (STIB) trial

Abstract: Aims: The Stent Thrombosis In Belgium (STIB) trial aimed to determine whether assessing platelet reactivity (PR) in patients with stable coronary artery disease undergoing elective percutaneous coronary intervention (PCI) could predict the risk of ischaemic complications and adverse clinical events up to 30 days post PCI.Methods and results: PR before intervention was determined in 891 patients undergoing PCI for stable angina pectoris. Twelve to 24 hours before PCI, all patients received a 600 mg clopidogrel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…One-month results of the STIB trial showed that HPR was not predictive of early ischaemic events in patients with stable angina undergoing planned PCI, although HPR to clopidogrel was observed in 50% of these patients using the point-of-care VerifyNow® test 4 . These data contrast with the observations made in patients undergoing PCI for unstable coronary syndromes 5 .…”
Section: Although Clinical Value and Impact Of Individuallymentioning
confidence: 97%
“…One-month results of the STIB trial showed that HPR was not predictive of early ischaemic events in patients with stable angina undergoing planned PCI, although HPR to clopidogrel was observed in 50% of these patients using the point-of-care VerifyNow® test 4 . These data contrast with the observations made in patients undergoing PCI for unstable coronary syndromes 5 .…”
Section: Although Clinical Value and Impact Of Individuallymentioning
confidence: 97%
“…Therefore, a strong and broad effort is ongoing to identify reliable biomarkers indicative of future major adverse clinical events (MACE). Unfortunately, in real-life clinical scenarios, the practical utilization of predictive models is quite limited and many reports are pessimistic, suggesting marked discrepancies between interventional cardiologists' estimates and the established theoretical prediction models, scores or biomarkers [3,4,5]. Furthermore, the data are very scarce with regard to the potential association of antiplatelet therapy and future MACE predictions.…”
Section: Introductionmentioning
confidence: 98%
“…Strong data suggest that aspirin-resistant patients have a 4-fold greater risk of suffering from stroke [5,17] . Therefore, further studies will have to evaluate the place of APD efficacy testing and APD reinforcement in the specific context of acute or chronic inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%